О понятии “каузативный глагол” - Карпувене, Г. (Kalbotyra, 1988)
The term ‘causative verb’ finds different interpretations in linguistics. Various types of causative verbs have been distinguished by linguists, their morphological, syntactical and semantic classifications have been worked out. Still, there is no full agreement on what is to be regarded a causative verb. For example, it is by the formal criterion entirely and with certain inconsistency that the class of causative verbs is distinguished in the works of Lithuanian linguists and in dictionaries. The present paper is concerned with pointing out such inconsistencies and argues that there are pairs of morphologically unrelated verbs in every language which stand in the same semantic relation of causality to one another as do pairs of verbs that are related by means of productive morphological formations. The author maintains that any verb with the semantic component ‘CAUSE’ in its meaning should be considered a causative verb.